Evaluación comparativa de la microdureza superficial entre resinas acrílicas y bisacrílicas expuestas a una bebida carbonatada. Estudio in vitro. - Gaona Yupangui, Joselyn Brigitte (2024)
In dentistry, the selection of material for provisional crowns is a critical factor in determining the durability and resistance of temporary restorations. This study aimed to analyze the surface microhardness of acrylic and bis-acrylic resins comparatively under exposure to a carbonated beverage through an in vitro study. Four groups of 10 samples each were evaluated and divided into two control and two experimental groups. Statistical tests were applied to assess changes in microhardness before and after exposure to the experimental agent. The results revealed notable differences between the materials studied. Polymethyl methacrylate (PMMA) resin exhibited a microhardness of 12.21 HV, significantly surpassing the 8.81 HV of the bis-acrylic resin. Both materials experienced a reduction in surface microhardness, though with essential variations. The bis-acrylic resin showed a less pronounced decrease, whereas PMMA exhibited more significant alteration after exposure to the carbonated beverage. These findings suggest that PMMA could be more suitable for applications requiring high resistance. The selection of temporary restoration materials should consider not only their initial properties but also their behavior under conditions simulating the oral environment. In conclusion, exposure to carbonated beverages directly impacted the microhardness of the analyzed materials, highlighting the importance of selecting materials that maintain their structural integrity under different conditions of chemical stress.